2023
DOI: 10.1007/s00421-023-05269-2
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of a home-based isometric wall squat intervention using ratings of perceived exertion to select and control exercise intensity: a pilot study in normotensive and pre-hypertensive adults

Abstract: Purpose Isometric exercise (IE) and isometric wall squat (IWS) training have been shown to be effective methods of reducing arterial blood pressure. However, most IE interventions require methodologies and equipment that could present a barrier to participation. Therefore, this study aimed to examine the effectiveness of an accessible RPE prescribed IWS intervention. Methods Thirty normotensive and pre-hypertensive adults were randomly assigned to a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…This presents logistical concerns when considering the ultimate objective of widespread clinical implementation, especially given the straightforward process of prescribing handgrip IET at 30% MVC. However, new evidence demonstrates the effectiveness of a rate of perceived exertion (RPE)-prescribed wall squat intervention which presents a more practical prescription approach [61]. Interestingly, recent acute research reported significantly higher RPE values during a single handgrip session compared with wall squat, which may carry implications for long-term adherence [62].…”
Section: Modementioning
confidence: 99%
“…This presents logistical concerns when considering the ultimate objective of widespread clinical implementation, especially given the straightforward process of prescribing handgrip IET at 30% MVC. However, new evidence demonstrates the effectiveness of a rate of perceived exertion (RPE)-prescribed wall squat intervention which presents a more practical prescription approach [61]. Interestingly, recent acute research reported significantly higher RPE values during a single handgrip session compared with wall squat, which may carry implications for long-term adherence [62].…”
Section: Modementioning
confidence: 99%